Mothers' Sensitivity To Their Infants' Needs: An Exploration Of Influencing Factors In The First Six Months - Srinatania, Dewi; Desiani, Bela; Perdani, Agni Laili; Hendra, Agus (Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI) Regional Jawa Barat, 2025)
Background: Childhood 0-6 months is a crucial time period in human development. Data on developmental delays in West Java in 2024 show that around 30% of children in West Java experience developmental delays, with around 80% due to lack of stimulation. Stunting, which is a form of development delay, is also targeted to decrease significantly in West Java, from 21.7% to 14-15% in 2024. The relationship between mother and child is a context of maternal sensitivity. A sensitive mother will respond quickly and appropriately to the needs of the child, provide warm attention, and create a strong emotional bond between mother and child which is an important foundation for the child's future social and emotional development. Objective: to find out what factors can influence maternal sensitivity in babies aged 0-6 months. Method: this research uses quantitative research methods,With a total sample of 113 respondents, the sampling technique in this study used a non-probability sampling technique and the criteria for respondents were mothers who had babies aged 0-6 months using the NACTS (Nursing Child Assessment Teaching Scale) questionnaire. The CVI of maternal sensitivity scale ranged between 0.80 to 1.00. After reviewing the items (N = 36), the S-CVI was 0.87 for clarity and the S-CVI was 0.9 Results: The results show a p-value <0.05 for the variables number of children and family income. From this, it can be concluded that the factors that influence maternal sensitivity are these two variables. Conclusion: Of the several factors that influence maternal sensitivity, namely the number of children and family income are the most influential.